1999
DOI: 10.1002/(sici)1099-1220(199911/12)5:6<411::aid-ijpg150>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing changes in interstate migration patterns of the United States elderly population, 1965-1990

Abstract: This study examines temporal changes in elderly interstate migration in the United States. All of the interstate movers who were 60 and over are selected from the Public Use Micro‐Samples (PUMS) of the 1970, 1980 and 1990 censuses, and three interstate mobility tables are constructed. A triply‐constrained gravity model is used to compare the propensities of moving to southern destinations while controlling population sizes for origins, destinations and sample years. The results show that the propensity for mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Destination preferences in the US have changed over the last 30 years. Lin (1999) reported that the propensity to move from cold to warm areas has decreased since 1980, and the traditional retirement states of Florida, Arizona and California are now joined by other popular retirement states in the south and southwest. Movement out of urban areas was confirmed by Fuguitt and Beale (1993); metropolitan areas lost and non-metropolitan areas gained elderly migrants.…”
Section: Past Researchmentioning
confidence: 99%
“…Destination preferences in the US have changed over the last 30 years. Lin (1999) reported that the propensity to move from cold to warm areas has decreased since 1980, and the traditional retirement states of Florida, Arizona and California are now joined by other popular retirement states in the south and southwest. Movement out of urban areas was confirmed by Fuguitt and Beale (1993); metropolitan areas lost and non-metropolitan areas gained elderly migrants.…”
Section: Past Researchmentioning
confidence: 99%
“…Other major destinations include Texas, Colorado, the coastal areas of the Southeast and the Pacific Northwest, the Ozarks (Arkansas and Missouri), and the lake regions of the North Central states. Although retirement migration from the North to the Sunbelt may have subsided somewhat during the 1980s, the major regional patterns established during the past few decades have continued to the present day (Fuguitt and Beale 1993;Golant 1990b;Graff and Wiseman 1990;Lin 1999;Longino 1995;Rex 1996;Rogers 1992). Frey et al (2000) identify the most popular destination states for various groups of elderly interstate migrants.…”
Section: Regional Patterns Of Later-life Migrationmentioning
confidence: 99%
“…Moreover, all of these studies investigate migrant characteristics at one point in time. In contrast, research that studies changes in elderly migration over time has focused on the frequency and geographic distribution of interstate moves (e.g., Conway and Rork 2010;Flynn et al 1985;Lin 1999;Longino and Bradley 2003). Most find fairly stable geographic patterns and lend support to Wolf and Longino's (2005) dispute of our "increasingly mobile" society.…”
Section: Introductionmentioning
confidence: 87%